External Quality Assessment Practices in Clinical Biochemistry Laboratory: What is the need? - Niraula, A.; Bataju, M. (Kathmandu University Medical Journal, 2020)
Health Care services is considered as an amalgamation between the doctor undergoing the examination and laboratory personnel behind the proper diagnosis of the patient. It has evolved to a large extent from a simple process of examination to handling the prescription to the patient. During this evolution, there has been a remarkable development in the field of laboratory diagnosis. A good laboratory is abided by the rule of quality services including quality control; both internal and external. External quality assessment program contributes to the long term accuracy of the analytical method used by the laboratory. It determines the number of quality element of the practicing laboratory and helps in the upliftment of the status of the laboratory to laboratory accreditation and certification. This review article is intended to review the importance of the external quality assessment program over internal quality control, its need in the laboratory and the current practices in external quality assessment. Medline search was done for the articles published in English language from 1945 to 2018. Keywords employed to search the articles were external quality assessment, EQA programs, quality assurance, and quality control in clinical biochemistry, respectively. We searched for any articles with the details of external quality assessment tools that were original articles, review, editorial and the official website of the EQAS program. The unavailable articles were searched through research gate and the authors were requested for full text. A total of 5 full text original research article were found and rest of the articles like review article, editorial, national policy were studied in detail. Standard textbooks for clinical chemistry and chapters for EQA under quality assurance was reread in detail. Studies and policy makers have depicted that External Quality Assessment scheme (EQAS) as an integral component for the efficient and high quality laboratory operation. The western countries haizve their own laboratory accreditation body which conducts the EQAS program and offers participation to other clinical laboratories. Countries in South East Asia have shown to be burgeoning in the field of EQA program with establishment of their own laboratory accreditation bodies and incorporating the non-accredited laboratories in EQA programs.